Pengembangan Sistem Pemanenan Air Hujan untuk Penyediaan Air Bersih di Selatpanjang Riau - Eko Sutrisno; Yusni Ikhwan Siregar; Nofrizal Nofrizal (Universitas Riau, 2016)
Abstract: The research was conducted from March to June 2015 during the rainy season and the Village were located in four Selatpanjang South Village, East Selatpanjang, Selatpanjang City and West Selatpanjang Tebing Tinggi District of Riau Kepulauan Meranti. The purpose of this study was to analyze the potential availability of rainwater, water needs population in the region Selatpanjang 2030, the development of rainwater harvesting systems and outlines the relationship with environmental, social and economic. The method used in this study was the observation by analyzing rainfall, debit mainstay, drainage coefficient (α), population projections, the ratio of the number of residents with clean water needs as well as rainwater harvesting design. The results showed that the potential of rainwater in the area amounted to an average Selatpanjang 1724.8 mm/year, of the four sub regions Selatpanjang rain water can be harvested amounted to 17.248 billion liters/year. The four village Selatpanjang region in 2030 amounted 49 471 inhabitants population in predicted, so, it is necessary to clean water for 534 286 800 liters for three months. So if managed and well developed, the rain water can meet the need of clean water Selatpanjang community throughout the year. How to manage it is by developing the rainwater harvesting system with a system of individual, communal for three families and communal for five families and build ponds to accommodate the run-off. Economically, the use of rainwater harvesting system is cheaper than buying water each summer, primarily communal system for three families. Socially aspects that bring positive habits and reduce conflicts between neighbors and the environment, with the principle of sustainable utilization of natural resources. The quality of rain water in Selatpanjang meets the criteria for clean water, so it can be used as a source of clean water.